Development of a mathematical model of measuring control device of natural gas humidity - Bilynsky, Yosyp; Horodetska, Oksana; Novytskyi, Dmytro; Voytsekhovska, Olena (Technology audit and production reserves, 2020)
The object of research is the measuring control of the humidity of natural gas. There are many methods and devises of determining humidity that are used in laboratory measurements under normal conditions. However, in practice, it is necessary to measure humidity over a wide range of pressure and temperature, as well as at high and medium pressure in the gas pipeline. Such use requires the development of sensors that are reliable, stable and resistant to contamination and high pressures. Due to their simple, reliable design and rather high accuracy of measurement, humidity meters based on the use of the microwave method have been widely used. Based on the studies, a devise for measuring the humidity of natural gas is proposed on the basis of a microwave method for measuring humidity, in which, unlike the known methods, the use of a traveling wave in a waveguide is proposed. And changes in the dielectric properties of gases during their interaction with microwave waves are estimated. Studies have been carried out that showed that the presence of a comparative channel made it possible to increase the measurement accuracy, since a two-channel system, unlike a single-channel system, eliminates the instability of the value of the input signal supplied by the generator. The principle of operation of measuring control device of natural gas humidity is described, which contains a microwave generator, attenuators, waveguide tees, a waveguide comparison section, a temperature and pressure sensor, switches for comparative and measuring channels, a measuring cell, amplifier, processor, indicator. A mathematical model of the measuring control device of natural gas humidity has been developed, which takes into account the value of the dielectric constant of the gas of the measuring and reference channels, and contains temperature correction coefficients, the use of which allows to increase the accuracy of humidity measurement. The research results allow to argue about the prospects for the practical application of measuring the natural gas humidity based on the microwave traveling wave method.